Finishing and polishing effects of multiblade burs on the surface texture of 5 resin composites: microhardness and roughness testing - Elodie Ehrmann; Etienne Medioni; Nathalie Brulat-Bouchard (Restorative Dentistry & Endodontics)
ObjectivesThe aim of this in vitro study was to test the effect of 2 finishing–polishing sequences (QB, combining a 12/15-fluted finishing bur and an EVO-Light polisher; QWB, adding a 30-fluted polishing bur after the 12/15-fluted finishing bur used in the QB sequence) on 5 nanotech-based resin composites (Filtek Z500, Ceram X Mono, Ceram X Duo, Tetric Evoceram, and Tetric Evoceram Bulk Fill) by comparing their final surface roughness and hardness values to those of a Mylar strip control group (MS).Materials and MethodsTwelve specimens of each nanocomposite were prepared in Teflon moulds. The surface of each resin composite was finished with QB (5 samples), QWB (5 samples), or MS (2 samples), and then evaluated (60 samples). Roughness was analysed with an optical profilometer, microhardness was tested with a Vickers indenter, and the surfaces were examined by optical and scanning electron microscopy. Data were analysed using the Kruskal-Wallis test (p < 0.05) followed by the Dunn test.ResultsFor the hardness and roughness of nanocomposite resin, the QWB sequence was significantly more effective than QB (p < 0.05). The Filtek Z500 showed significantly harder surfaces regardless of the finishing–polishing sequence (p < 0.05).ConclusionsQWB yielded the best values of surface roughness and hardness. The hardness and roughness of the 5 nanocomposites presented less significant differences when QWB was used.